(3GdeMce hGdeMjW GdCYXes - (3Ydj Hf ESeGYjd, GdeYQha HGHf pSjnOg, CHh GdMSf , GdVQjQ GdCfOdSj,J (B458 (3g` s ((3YHO Gddg Hf SdjeGf Hf eMeO s)
(3ChdgG (B:s
(3GdVGO hGdHGA (B: (3GdVH ef GdMTQGJ eYQha hgh jTHg GdhQd hGdLeY CVH hVHGH hVHGf s
(3BNQgG (B:s
(3GdYXje ef GdjYGSjH OhjHI cGdMLd cdGH ebdhH GdSeQI efRdI hGdShGO jchf Pdc ai GdfGS Pdc eeG jbHdgG , EdG Cf GdCOeI CcKQ s
(3fSNI SGHYIs
(3HChQGbgG GdCNjQI bWYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B209 s
(3eUOQ GbJfGA GdCUd (B:s
(3TgjO Ydi (B(2679) s
Keywords: (3GddZIs